Recency Effects in the Auditor's Belief-Revision Process. - Tubbs, Richard M.; Messier, William F. (The Accounting Review, 1990)
Tests the predictions of a descriptive model of sequential belief revision using content-rich audit scenarios. Characteristics of auditing as a sequential process; Prediction of the model in which an auditor obtains and evaluates evidence; Testing of lack of order effect.